Middle income household spending patterns on housing in Malaysian state capital cities: where does all the money go? - Rusli Latimaha; Zakaria Bahari; Nor Asmat Ismail (Penerbit Universiti Kebangsaan Malaysia, 2019)
This paper examines the factors influencing the expenditure pattern of middle-income households on housing in selected state capital cities in Malaysia by focusing on mortgage and rental expenses. Three state capital cities were chosen (George Town in Pulau Pinang, Kuala Lumpur and Johor Bahru in Johor) and a survey was carried out with 473 observations that were used for estimations by using a censored Tobit model. The results indicate that household income is statistically significant and does indeed affect mortgages but not the rental expenses in the selected state capital cities. Moreover, there is strong evidence of a relationship between family size and the number of rooms with the mortgage and rental expenditure. The analysis also indicates that there is a different pattern of expenditure on mortgage and rental between the different ethnic groups in Malaysia. The Chinese and Indian races tend to spend more on mortgages and less on rental compared to the Malays. Further, the gender and age of household heads are found to be insignificant in terms of influencing mortgages but do affect rental expenditure. In addition, middle-income households in Johor Bahru pay more on mortgages and in Kuala Lumpur such households pay more for housing rental. It is concluded that changes in spending patterns are starkly different across state capital cities in Malaysia and mortgage repayments represent a large proportion of household expenditure.